2016
DOI: 10.1007/s00586-016-4376-9
|View full text |Cite
|
Sign up to set email alerts
|

Are non-invasive interventions effective for the management of headaches associated with neck pain? An update of the Bone and Joint Decade Task Force on Neck Pain and Its Associated Disorders by the Ontario Protocol for Traffic Injury Management (OPTIMa) Collaboration

Abstract: The management of headaches associated with neck pain should include exercise. Patients who suffer from chronic tension-type headaches may also benefit from relaxation training with stress coping therapy or multimodal care. Patients with cervicogenic headache may also benefit from a course of manual therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 65 publications
4
36
0
2
Order By: Relevance
“…The Guideline Expert Panel did not recommend these interventions to minimize the risk of iatrogenic disability in patients with neck pain (Cassidy, Carroll, Côté, & Frank, ; Côté et al, ; Côté & Soklaridis, ). We found inconclusive evidence on the effectiveness of needle acupuncture for the management of tension‐type headaches because the results of multiple high‐quality RCTs conflicted with each other (Varatharajan et al, ). The guideline does not recommend passive physical modalities, stand‐alone structured patient education or work disability prevention interventions because their effectiveness has not been evaluated in high‐quality studies (Varatharajan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Guideline Expert Panel did not recommend these interventions to minimize the risk of iatrogenic disability in patients with neck pain (Cassidy, Carroll, Côté, & Frank, ; Côté et al, ; Côté & Soklaridis, ). We found inconclusive evidence on the effectiveness of needle acupuncture for the management of tension‐type headaches because the results of multiple high‐quality RCTs conflicted with each other (Varatharajan et al, ). The guideline does not recommend passive physical modalities, stand‐alone structured patient education or work disability prevention interventions because their effectiveness has not been evaluated in high‐quality studies (Varatharajan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We updated the systematic reviews from the Bone and Joint Decade 2000–2010 Task Force on Neck Pain and Its Associated Disorders (Hurwitz et al, ). This update included six systematic reviews (published in one article) examining the effectiveness and safety of non‐invasive interventions for the management of headaches associated with neck pain (Varatharajan et al, ). We also conducted one systematic review examining cost‐effectiveness of the non‐invasive interventions (data extraction completed but not published).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported a high correlation (r = 0.67-0.83) between neck disability (evaluated using the Neck Disability Index (NDI) and the Northwick Park Neck Pain Questionnaire (NPQ)) and disability of the upper limb (evaluated using the Disability of the Arm, Shoulder, and Hand (DASH) questionnaire (Huisstede et al, 2009;Mehta et al, 2010;Osborn and Jull 2013) indicating a relationship between neck pain and upper limb disability. Although the exact mechanism between impaired upper limb function and neck pain has not been extensively researched, studies investigating the efficacy of exercise for the treatment of neck pain and headaches usually include shoulder girdle and upper limb exercises in their exercise protocols (Amorim et al, 2014;Ang et al, 2009;Bronfort et al, 2001;Franca et al, 2008;Jull et al, 2002;Kay et al, 2012;Varatharajan et al, 2016). To understand how upper limb function (or dysfunction) may affect the neck region and potentially result in neck pain, it is necessary to consider the anatomical connection between these two regions.…”
Section: Study 1 (Chapter 3)mentioning
confidence: 99%